Pengaruh Konsentrasi Rootone-F Terhadap Pertumbuhan Stek Dombeya Wallichii (Lindl.) Benth Ex. Baill - Elly Proklamasiningsih; Iman Budisantoso; Azhara Restuaji Maharani (Fakultas Biologi Universitas Jenderal Soedirman, 2025)
Dombeya wallichii (Lindl.) Benth ex. Baill. is a flowering plant that is widely used as an ornamental plant and to support honey bee cultivation because of its abundant flowers with attractive shapes and colours. Plant propagation through cuttings is often done to maintain the superior traits of the parent plant. Rootone-F, which contains growth regulators, is known to be effective in stimulating root growth in cuttings of various plants. The objectives of this study were to examine the effect of Rootone-F on the growth of D. wallichii stem cuttings and to determine the most effective concentration of Rootone-F in stimulating the growth of D. wallichii stem cuttings. The study was conducted at Cilengko Farm Pabuaran, Purwokerto, from May to August using a split-plot randomised design. The main plots consisted of the third, fourth, and fifth branches. The subplots consisted of Rootone-F concentrations of 0 mg/l (control), 50 mg/l, 100 mg/l, and 150 ppm. The blocks or replicates consisted of the base, middle, and tip. The data obtained were analysed using ANOVA at 5% and 1% levels and DMRT test at 5% level. The results showed that the application of Rootone-F had a very significant effect on the number of roots and a significant effect on root length at 12 weeks after planting. The best Rootone-F concentration was 100 ppm for root number and root length growth. The best cutting position was taken from the top section.